Percepção Espacial / Visuomotora Associada Ao Processamento Auditivo Em Crianças Na Fase Escolar: Intervenção E Reedução - Goncalves, Fatima Aparecida [UNIFESP] (2017)
Abstract: The discrepancy in temporal and spatial/motor orientation is pointed out in the literature as co-occurring in learning disorder cases. However, educational and therapeutical practices focus temporal stimulation, which is directly linked to language mechanisms, whereas despite acknowledged as associated, spatial/motor orientation is not emphasized. Researches show that both plasticity and maturation of sensory and perceptual systems are affected by stimulation, once stimulus and experience activate and reinforce specific neural pathways. This study brings a multisensory therapeutical/educational intervention group approach, held inside the school to improve auditory perceptual capacity and spatial and motor organization of the school age child as well as social interaction in small groups. Objective: this paper aims to verify the efficacyduto of an intervention program involving spatial/motor and auditory intervention in children from ages 9 to 11, with no cognitive alterations. Method: 162 children from public schools, from both genders, considered cognitively adequate according to Raven Progressive Matrix (1992) were divided into four groups: three experimental groups: multisensory group; auditory/motor group; and motor/auditory group - which received stimulation sessions; and a control group without stimulation. All groups were evaluated by means of Motor Development Scale; Simplified Evaluation of Central Auditory Processing; Visuospatial Test from Luria/Nebraska Neuropsychological Battery and Scale of auditory behaviors (SAB). The experimental groups were evaluated and re-evaluated after eight weeks without intervention. They then received different types of intervention involving auditory and spatial/motor aspects combined and isolated. They were re-evaluated after eight stimulation sessions (4 weeks) so that the groups of isolated stimulation could change the stimulated aspect and once more, after eight more stimulation sessions (4 more weeks). The control group was evaluated in the beginning of the program and re-evaluated after 16 weeks. Results: in the experimental groups, there was significant effect (p < 0,01) in comparison between instants with and without intervention in relation to variables which were: balance, spatial organization, temporal organization and transition of time structures (dictation) on the motor scale; verbal and nonverbal sequential memory; and for the score referring to the auditory, attention, and total score in SAB. There was no statistical significance in the variables of the visuospatial test. There was also a significant effect in the comparison between intervention groups on the following variables: temporal organization (p<0,01) and score referring to the attention aspect and total score in SAB scale (p<0,02). Conclusion: The three experimental groups benefited from the intervention, especially after the first eight sessions of stimulation (4 hours training), with more significance to the groups of isolated stimulation, auditory/motor and motor/auditory. The experimental groups differed statistically from the control group on most studied aspects.